Relationship between cardiovascular health metrics and physical performance in community-living people: Results from the Longevity check-up (Lookup) 7+ project. Issue 1 (December 2018) - Landi, Francesco; Calvani, Riccardo; Picca, Anna; Tosato, Matteo; D'Angelo, Emanuela; Martone, Anna; Serafini, Elisabetta; Ortolani, Elena; Savera, Giulia; Salini, Sara; Acampora, Nicola; Bernabei, Roberto; et al.
Abstract Cardiovascular health metrics (CHMs) may predict disability independent of vascular events. Though, the link between CHMs and physical performance is unclear. This relationship was explored using data from the Longevity check-up (Lookup) 7+ project. Lookup 7+ is an ongoing cross-sectional survey conducted in unconventional settings across Italy. People who are at least 18-year-old and provide written informed consent are eligible. CHMs [i.e., smoking status, healthy diet, body mass index (BMI), blood pressure, blood cholesterol, and diabetes status] are assessed through closed questions and objective measurements. Physical performance is measured via the 5-repetition chair-stand test. Analyses included 7446 participants (55.5 ± 14.9 years; 56% women). Physical performance positively correlated with CHMs scores, such that participants who scored higher (6–7 points) completed the chair-stand test about 2 s faster than those scoring lower (1–2 points). In fully adjusted analysis, better physical performance was more frequently observed in younger, non-smoking, physically active men, with ideal BMI, and no diabetes. Our findings indicate a gradient of better physical function with increasing CHMs scores. Future investigations should establish the longitudinal effect of unhealthy behaviours and cardiovascular risk factors on physical performance and verify whether implementation of large-scale primordial cardiovascular prevention may positively impact physical fitness.